Comparative Performance of Mango Varieties Grafted on Vellaikolamban and Mixed Rootstock - Gawankar, M S; Salvi, B R; Chavan, S A; Dalvi, N V (Journal of Horticultural Sciences, 2010)
Research on rootstock in mango is very limited in our country. Kalapady was reported to be a dwarfing rootstock. Recent trend among mango growers is to high density orcharding with dwarfening nature of the varietie. Efforts were made at Agriculture Research Station, Mulde, to study comparative performance of Ratna, Alphonso and Kesar mango on Vellaikolamban and mixed rootstock i.e., heterozygous seedling stock and the effect of rootstock on a scion under high density of 5m x 5m spacing. Results indicated that use of Vellaikolamban rootstock reduced plant volume in scion cv. Alphonso by 39.1%, followed by 24.9% in Ratna and 26.5% in cv. Kesar. As volume of the canopy was reduced, it directly influenced fruit yield cvs. Alphonso and Ratna. However, reduction in canopy volume had a positive influence on yield in cv. Kesar. Net returns of Rs.38,629/- per ha were maximum for Kesar with the rootstock Vellaikolamban.